PENGARUH CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mia Sulistia Nengsih; Edi Sutanto; Nurhaini (Universitas La Tansa Mashiro, 2023)
The aim of this research is to analyze the influence of Corporate Governance using the proxies taken (Institutional Ownership, Audit Committee and Independent Commissioners) and Company Size on Company Value in Primary Consumer Goods Sector Companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2021 period. The population of this research includes Primary Consumer Goods Sector companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2021 period. The method used in this research is quantitative methods. The sampling technique used purposive sampling technique, based on the specified criteria, a sample of 34 companies was obtained with a total of 136 observation data. The method used in this research is multiple linear regression analysis. The results of this research prove that Institutional Ownership partially has an effect on Company Value, the Audit Committee has a partial effect on Company Value, Independent Commissioners have a partial effect on Company Value, and Company Size has a partial effect on Company Value. The results of the simultaneous test state that the variables Institutional Ownership, Audit Committee, Independent Commissioners, and Company Size simultaneously influence Company Value.